2011
DOI: 10.1590/s0066-782x2011005000020
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do vinho tinto associado ao exercício físico no sistema cardiovascular de ratos espontaneamente hipertensos

Abstract: Background: Physical exercise (PE) is effective in the treatment and prevention of hypertension associated with improved lipid profile and cardiac contractile function. Regular and moderate consumption of alcoholic beverages such as red wine brings a cardiovascular protective effect. Beverage-derived polyphenols have antioxidant properties benefiting blood vessels. There is little evidence on the consumption of red wine associated with PE and the influences on the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Achados incluindo a investigação de fitoquímicos e flavonoides, principalmente o resveratrol e a quercetina, demonstraram melhora na hipertrofia cardíaca ventricular esquerda in vivo e in vitro (Ryu et al, 2016). Um estudo sobre as alterações fisiológicas a respeito da fração de ejeção do ventrículo esquerdo verificou que não ocorreu influência das intervenções aplicadas por meio do consumo moderado de vinho (Soares Filho et al, 2011) assim como em nosso estudo.…”
Section: Discussionunclassified
“…Achados incluindo a investigação de fitoquímicos e flavonoides, principalmente o resveratrol e a quercetina, demonstraram melhora na hipertrofia cardíaca ventricular esquerda in vivo e in vitro (Ryu et al, 2016). Um estudo sobre as alterações fisiológicas a respeito da fração de ejeção do ventrículo esquerdo verificou que não ocorreu influência das intervenções aplicadas por meio do consumo moderado de vinho (Soares Filho et al, 2011) assim como em nosso estudo.…”
Section: Discussionunclassified
“…This total was rounded up to 40 animals, divided in five experimental groups: 1) CIR group -treated with 3.715 mL/kg/day of saline solution 0.9%, n = 8; 2) CIR+RES group -treated with RES 1 mg/kg/day, n = 8; 3) CIR+GJ group -treated with 3.715 mL/kg/day of Aurora ® whole GJ, n = 8; 4) CIR+ethanol (ET) group -treated with 3.715 mL/kg/day of 12.5% ethanol solution, n = 8; 5) CIR+RW group -treated with 3.715 mL/kg/day of RW (Malbec Wine, Valdorella®, containing 12.5% ethanol, n = 8). The doses administered to the animals corresponded, approximately, to 300 mL of GJ and RW consumed by humans, dose equivalent to 1.3 mg/L of polyphenols, including the RES 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Mix 1 and Mix 2 diets, which were hypercholesterolemic, showed an increase of HDL in the blood of rats by 22.3% and 32.6%, respectively. In the study by Soares-Filho et al (2011), rats consuming moderate amounts of red wine showed an increase of 6.63% in the serum levels of HDL, compared with rats consuming the control diet. Helbig (2007) found a rate of 38.29% in blood levels of HDL in rats fed parboiled rice.…”
Section: Total Cholesterol High Density Lipoprotein (Hdl) Low Densimentioning
confidence: 96%